KETERLIBATAN TOKOH MELAYU DALAM PILKADA DI KOTA PALEMBANG SUMATRA SELATAN - Darmawan Z (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
This article discusses the involvement of Malay leaders in 2018 regional head elections in Palembang City. The character will play a very important role in winning the battle between political parties in the city of Palembang, traditional factors and local leaders play a role. While traditional leaders and religious leaders, have their own influence for society. Malay community leaders are people who have influence and are respected by the community because of the wealth of their knowledge. The role of the involvement of Malay cultural figures on the electability of candidates for the Regional Head in Palembang City, it is known that many ulama and community leaders were made as success teams as well as the main supporters of each candidate pair of mayors / deputy mayors of Palembang. Local politics is increasingly developing as a snowball-like force that is increasingly growing as a force that can influence the political system in Palembang City